Vitamins and minerals bio-fortification of edible plants - Benkeblia, Noureddine (Hoboken, NJ : Wiley, 2020)
"This book will report on specific biofortification of edible crops using modern biotechnology and omics technologies in their broad and targeted sense. This discipline is attracting the interests of the scientific community who are involved in the development of novel biofortified edible crops, describing how the modern biotechnological tools and omics technologies can be used to improve the nutritional characteristics and nutritional health benefits of edible plants focusing on vitamins and minerals. Some work have been published on phytonutrients enhancement of crops, but few work reported on vitamins and minerals. This book will include, but is not limited to, modification and enhancement of edible crops at the molecular level, frequently dubbed as "modern biotechnology" or "Omics technologies". This book will also concentrate on recent developments of biotechnology used in edible development and will present biotechnology and omics as provider of powerful and useful tools, in a continuum of technical evolution that contributes or could contribute to the improvement of nutritional quality of edible crops"--
Biofortification of Edible Plants: Set the Stage for Better Nutrition -- Food Fortification: What's in it for the malnourished world? -- Modern Biotechnologies and Mineral Biofortification of Edible Crops -- Biotechnologies and Vitamins Biofortification of Edible Crops -- Carotenoids Biofortification of Sweetpotato -- Improving iron nutrition in plant foods: the role of legumes and soil microbes -- Biofortification of carotenoids in agricultural and horticultural crops: A promising strategy to target vitamin A malnutrition -- Agronomic Biofortification from a Stakeholder's Viewpoint: Evidence from studies on Iodine Enriched Foods in Uganda -- Biofortification of Cereals through Foliar Application of Minerals -- NAS Overexpression and Rice Zinc Biofortification: An Insight, Current Knowledge and Outlook.
Includes index.
Keywords: Crop improvement; Food crops -- Biotechnology; Plants, Edible; Enriched foods; Electronic books